A Review of Cannabis and Interactions With Anticoagulant and Antiplatelet Agents. (13th November 2019) - Greger, Jessica; Bates, Vernice; Mechtler, Laszlo; Gengo, Fran
Abstract: Legalization of medical cannabis has occurred in 33 states and the District of Columbia, and recreational use has increased exponentially since 2013. As a result, it is important to understand how cannabis interacts with other drugs and has potential risks for patients on concomitant medications. Components of medical cannabis can inhibit or compete for several cytochrome P450 (CYP) hepatic isoenzymes, UDP‐glucuronosyltransferases, and P‐glycoprotein. These enzymes and transporters are involved in the metabolism and absorption of numerous medications, including anticoagulants (ACs) and antiplatelet agents (APs), potentially causing harmful drug‐drug interactions. ACs and/or APs are often prescribed to high‐risk patients with cardiac conditions, a history of myocardial infarction, or stroke. Cannabis may cause these medications to be less efficacious and put patients at risk for recurrent cardiovascular and cerebrovascular events. Several case reports show cannabis may inhibit the metabolism of warfarin because of CYP2C9 interactions, resulting in increased plasma concentrations, increased international normalized ratio, and risk of bleeding. Cannabidiol inhibits CYP2C19, an isoenzyme responsible for the transformation of clopidogrel to its active thiol metabolite. This interaction could lead to subtherapeutic levels of active metabolite and possibly increased stroke risk. Within this review, a total of 665 articles were screened from PubMed and EMBASE. Four case reports, 1 in vitro study, and 1 pharmacokinetic article were found to be of relevance. This review serves to examine reported and potential cannabis interactions with APs/ACs to help inform patients and health care providers of possible risks and knowledge gaps.